Vibrio Community Structure Shapes the Diversity of Carbenicillin‐Hydrolysing Class A β‐Lactamase Circulating in European Coastal Environments - Berenice Reggiardo; Jamal Saad; Marie‐Agnès Travers; Yannick Labreuche; David Goudenège; Eve Toulza; Coralie Broquard; Karl B. Andree; Julia Mougin; Nicolas Argenta; Gaëlle Courtay; Juliette Pouzadoux; et al. (Environmental Microbiology, 2026)
Coastal environments are increasingly recognised as reservoirs of known antibiotic resistance genes (ARGs), but are less frequently identified as sources of novel ARGs. Here, we investigated class A β‐lactamases circulating in European coastal environments used for oyster farming. We examined their diversity, function, and the ecological factors associated with their geographic distribution and environmental dynamics. A high diversity of carbenicillinases was detected in the culturable microbiome of European oysters. The Harveyi and Splendidus clades were key Vibrio lineages structuring the geography of carbenicillinase diversity. The Harveyi clade was primarily associated with the circulation of known carbenicillinases in Mediterranean samples, whereas the Splendidus clade contributed previously uncharacterized carbenicillinase sequences across all Europe. A one‐year seasonal monitoring revealed that Vibrio alginolyticus drives the circulation of bla CARB‐42 in the Mediterranean Thau lagoon, with dynamics strongly associated with seawater temperature. bla CARB‐42 conferred intrinsic resistance to both carboxypenicillins and aminopenicillins in V. alginolyticus , which was found in most other species of the Harveyi clade with additional resistances to aztreonam, third‐generation cephalosporins and aminoglycosides. Since the Harveyi clade includes major human pathogens, these findings have direct implication for environmental and One Health surveillance, as rising seawater temperatures may increase coastal exposure to antibiotic‐resistant Harveyi clade Vibrio .

Vibrio splendidus O‐antigen structure: a trade‐off between virulence to oysters and resistance to grazers - Daniel Oyanedel; Yannick Labreuche; Maxime Bruto; Hajar Amraoui; Etienne Robino; Philippe Haffner; Tristan Rubio; Guillaume M. Charrière; Frédérique Le Roux; Delphine Destoumieux‐Garzón (Environmental Microbiology, 2020)
Summary A major debate in evolutionary biology is whether virulence is maintained as an adaptive trait and/or evolves to non‐virulence. In the environment, virulence traits of non‐obligatory parasites are subjected to diverse selective pressures and trade‐offs. Here, we focus on a population of Vibrio splendidus that displays moderate virulence for oysters. A MARTX (Multifunctional‐autoprocessing repeats‐in‐toxin) and a type‐six secretion system (T6SS) were found to be necessary for virulence toward oysters, while a region (wbe) involved in O‐antigen synthesis is necessary for resistance to predation against amoebae. Gene inactivation within the wbe region had major consequences on the O‐antigen structure, conferring lower immunogenicity, competitive advantage and increased virulence in oyster experimental infections. Therefore, O‐antigen structures that favour resistance to environmental predators result in an increased activation of the oyster immune system and a reduced virulence in that host. These trade‐offs likely contribute to maintaining O‐antigen diversity in the marine environment by favouring genomic plasticity of the wbe region. The results of this study indicate an evolution of V . splendidus towards moderate virulence as a compromise between fitness in the oyster as a host, and resistance to its predators in the environment.

Selection of Vibrio crassostreae relies on a plasmid expressing a type 6 secretion system cytotoxic for host immune cells - Damien Piel; Maxime Bruto; Adèle James; Yannick Labreuche; Christophe Lambert; Adrian Janicot; Sabine Chenivesse; Bruno Petton; K. Mathias Wegner; Candice Stoudmann; Melanie Blokesch; Frédérique Le Roux (Environmental Microbiology, 2020)
Summary Pacific oyster mortality syndrome affects juveniles of Crassostrea gigas oysters and threatens the sustainability of commercial and natural stocks of this species. Vibrio crassostreae ( V . crassostreae ) has been repeatedly isolated from diseased animals, and the majority of the strains have been demonstrated to be virulent for oysters. In this study, we showed that oyster farms exhibited a high prevalence of a virulence plasmid carried by V . crassostreae , while oysters, at an adult stage, were reservoirs of this virulent population. The pathogenicity of V . crassostreae depends on a novel transcriptional regulator, which activates the bidirectional promoter of a type 6 secretion system (T6SS) genes cluster. Both the T6SS and a second chromosomal virulence factor, r5 . 7 , are necessary for virulence but act independently to cause haemocyte (oyster immune cell) cytotoxicity. A phylogenetically closely related T6SS was identified in V . aestuarianus and V . tapetis , which infect adult oysters and clams respectively. We propose that haemocyte cytotoxicity is a lethality trait shared by a broad range of mollusc pathogens, and we speculate that T6SS was involved in parallel evolution of pathogen for molluscs.

The Role of the Glyoxylate Shunt in the Acclimation to Iron Limitation in Marine Heterotrophic Bacteria - Coco Koedooder; Audrey Guéneuguès; Rémy Van Geersdaële; Valérie Vergé; François-Yves Bouget; Yannick Labreuche; Ingrid Obernosterer; Stéphane Blain (Frontiers in Marine Science, 2018)

A single regulatory gene is sufficient to alter V ibrio aestuarianus pathogenicity in oysters - David Goudenège; Marie Agnès Travers; Astrid Lemire; Bruno Petton; Philippe Haffner; Yannick Labreuche; Delphine Tourbiez; Sophie Mangenot; Alexandra Calteau; Didier Mazel; Jean Louis Nicolas; Annick Jacq; et al. (Environmental Microbiology, 2015)
Summary Oyster diseases caused by pathogenic vibrios pose a major challenge to the sustainability of oyster farming. In F rance, since 2012 a disease affecting specifically adult oysters has been associated with the presence of V ibrio aestuarianus. Here, by combining genome comparison, phylogenetic analyses and high‐throughput infections of strains isolated before or during the recent outbreaks, we show that virulent strains cluster into two V . aestuarianus lineages independently of the sampling dates. The bacterial lethal dose was not different between strains isolated before or after 2012. Hence, the emergence of a new highly virulent clonal strain is unlikely. Each lineage comprises nearly identical strains, the majority of them being virulent, suggesting that within these phylogenetically coherent virulent lineages a few strains have lost their pathogenicity. Comparative genomics allowed the identification of a single frameshift in a non‐virulent strain. This mutation affects the varS gene that codes for a signal transduction histidine‐protein kinase. Genetic analyses confirmed that varS is necessary for infection of oysters and for a secreted metalloprotease expression. For the first time in a V ibrio species, we show here that VarS is a key factor of pathogenicity.

Virulence of an emerging pathogenic lineage of Vibrio nigripulchritudo is dependent on two plasmids - Frédérique Le Roux; Yannick Labreuche; Brigid M. Davis; Naeem Iqbal; Sophie Mangenot; Cyrille Goarant; Didier Mazel; Matthew K. Waldor (Environmental Microbiology, 2011)
Summary Vibrioses are the predominant bacterial infections in marine shrimp farms. Vibrio nigripulchritudo is an emerging pathogen of the cultured shrimp Litopenaeus stylirostris in New Caledonia and other regions in the Indo‐Pacific. The molecular determinants of V. nigripulchritudo pathogenicity are unknown; however, molecular epidemiological studies have revealed that recent pathogenic V. nigripulchritudo isolates from New Caledonia all cluster into a monophyletic clade and contain a small plasmid, pB1067. Here, we report that a large plasmid, pA1066 (247 kb), can also serve as a marker for virulent V. nigripulchritudo , and that an ancestral version of this plasmid was likely acquired prior to other virulence‐linked markers. Additionally, we demonstrate that pA1066 is critical for the full virulence of V. nigripulchritudo in several newly developed experimental models of infection. Plasmid pB1067 also contributes to virulence; only strains containing both plasmids induced the highest level of shrimp mortality. Thus, it appears that these plasmids, which are absent from non‐pathogenic isolates, may be driving forces, as well as markers, for the emergence of a pathogenic lineage of V. nigripulchritudo .